Echocardiographic monitoring for clozapine cardiac toxicity: lessons from real-world experience. (June 2013) - Murch, Stuart; Tran, Nga; Liew, Danny; Petrakis, Melissa; Prior, David; Castle, David
Objective: We aimed to identify the baseline prevalence of cardiac dysfunction in patients commencing clozapine, assess adherence with echocardiographic monitoring recommendations, and evaluate the utility and cost of echocardiographic monitoring for the development of clozapine-associated myocarditis and cardiomyopathy. Methods: A retrospective longitudinal cohort study was undertaken of 159 consecutive patients from a major tertiary centre commencing clozapine in the period January 2002 to July 2009. Results: Some 73% of patients had a baseline study, and 11% had a six-month follow-up study. Nine patients had abnormal left ventricular function at baseline. Myocarditis was identified in three patients, with all cases occurring within the first month of treatment and suspected on clinical grounds before an echocardiogram was performed. One case of possible cardiomyopathy was identified. The cost of echocardiographic screening in the first year of treatment was estimated at AUD 209, 356 per case of cardiomyopathy detected. Conclusion: The prevalence of cardiac dysfunction in patients commencing clozapine is high, and there are challenges in adhering with the recommended protocol for monitoring. Routine echocardiography is not useful in the detection of clozapine-associated myocarditis. Although cardiomyopathy may be identified, it is rare and associated with significant cost. Recommendations for routine echocardiographic monitoring should be re-examined.